Space Business (Springer Nature, 2024)
This book is an academic investigation of commercial activities of firms in the space related industries and those utilizing services provided by space technology firms. These firms and their activities are part of the “New Space” concept where space related commercial activities are undertaken and funded by private firms rather than government institutions. New Space is leading to business model innovation and new theory about space business activities including upstream and downstream commercial activities. Upstream value chains include activities prior to turnover of launched systems to operators. Downstream value chains include operation of systems in space as well as the transfer, processing, and sale of space-based data and data services. The commercial activities of space business now reach into everyday lives of most humans from banking and disaster management to resource monitoring to tourism. With such broad reach, the New Space ecosystem is rapidly developing in importance and complexity.